Anti-M 3 peptide IgG from Sjögren's syndrome triggers apoptosis in A253 cells - Reina, Silvia Lorena (2012)
Primary Sjögren´s syndrome (pSS) is an autoimmune disease that targets salivary and lachrymal glands, characterized by anti-cholinergic autoantibodies directed against the M3 muscarinic acetylcholine receptor (mAChR). The aim of this work was to evaluate if cholinergic autoantibodies contained in IgG purified from Sjögren sera could trigger apoptosis of A253 cell line. We also determined if caspase-3 and matrix metalloproteinase 3 (MMP-3) are involved in the induction of A253 cell death. Our results demonstrated that anti-cholinergic autoantibodies stimulate apoptosis and inositol phosphate (InsP) accumulation accompanied by caspase-3 activation and MMP-3 production. All of these effects were blunted by atropine and J104794, indicating that M3 mAChRs are impacted by the anti-cholinergic autoantibodies. The intracellular pathway leading to autoantibody-induced biological effects involves phospholipase C (PLC), calcium/calmodulin (CaM) and extracellular calcium as demonstrated by treatment with U-73122, W-7, verapamil, BAPTA and BAPTA-AM, all of which blocked the effects of the anti-cholinergic autoantibodies. In conclusion, anti-cholinergic autoantibodies in IgG purified from pSS patient´s sera mediates apoptosis of the A253 cell line in an InsP, caspase-3 and MMP-3 dependent manner.